ANTICOAGULANT TREATMENT OF AF: FOCUS ON THE WARFARIN DOSAGE - Y. Kovbasniuk; O. Plenova (Kazimierz Wielki University, 2015)
Kovbasniuk Yuriy, Plenova Olga. Anticoagulant treatment of af: focus on the warfarin dosage. Journal of Education, Health and Sport. 2015;5(10):323-326. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35295 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A323-326 https://pbn.nauka.gov.pl/works/679056 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 31.10.2015.   Anticoagulant treatment of AF: Focus on the warfarin dosage   Yuriy Kovbasniuk, Olga Plenova   National Medical University, Kyiv, Ukraine   Summary Authors analyzed the results of some studies of AF and warfarin dosing. Than investigation of 75 patient with AF (permanent type) was performed. According to demographic, anthropometric data and related conditions (diabetes mellitus type 2, myocardial infarction, acute cerebrovascular ischemia, pulmonary embolism, alcohol abuse - drinking more than one ounce of ≥3 weekly) predictive model of warfarin dosing was developed: warfarin dose = 0.097 * BMI - 0.03 * AGE + 0.30 *ASS.Status+ 0.02 *WC+ 1, 88. After testing of final model authors concluded what derived formula was representative, to determine the optimal dose of warfarin given to patient based on demographic characteristics. Considering all of the abovementioned, this model can be recommended for use determining the treatment strategy in patients with AF. Keywords: anticoagulant treatment, warfarin, atrial fibrillation.